Assessment of pet dogs as a reservoir of antibiotic resistant bacteria - Pillai, Deepti Kuttan (Kansas State University, 2011)
Transfer of bacteria, including antibiotic resistant strains between companion animals and people is likely due to close physical contacts. However, surveillance programs on prevalence of antibiotic resistance are focused mainly on food animals and very little is known about the role of companion animals in the development and spread of antibiotic resistant bacteria. For this study, enterococci were chosen as model organism due to intrinsic and acquired antibiotic resistance and several virulence traits that make them the 3rd most important nosocomial pathogens. In addition, increased fecal shedding of antibiotic resistant bacteria from stressed animals has been reported from studies on food animals. To determine whether the gut microbiota of pet animals serves as a reservoir of clinically important enterococci, 360 enterococcal isolates from two groups: healthy group and pyoderma (stressed) group with 9 dogs in each were identified and screened for resistance to 10 antibiotics and 4 virulence traits. The transferability of resistance determinants and clonality of selected isolates were assessed by horizontal gene transfer assays and pulsed-field gel electrophoresis, respectively. In addition, overall diversity of bacteria as well as antibiotic and metal resistance genes in feces of healthy dogs was assessed by tag-encoded parallel pyrosequencing and microarray analysis, respectively. The most prevalent enterococcal species identified was E. faecalis: healthy group (70.5%); pyoderma group (44.0%). In the pyoderma group, antibiotic resistance and virulence traits (esp, gelE) were more frequent than in the healthy group; however, the overall prevalence of antibiotic resistant strains was low (< 37%) in both groups. The most prevalent resistance genes were tet(M)and tet(S). The antibiotic resistance traits were transferable in-vitro in E. faecalis (tetracycline, erythromycin, doxycycline) and E. faecium (tetracycline). Genotyping revealed less diverse E. faecalis community in pyoderma infected dogs. Pyrosequencing (~7,500 sequences per dog) revealed Firmicutes as the dominant phylum and most common genera included Turicibacter, Lactobacillus, Ruminococcus, Clostridium, and Fusobacterium. Two phyla Lentisphaerae (<1%) and Fibrobacteres (<1%) are reported for the first time from healthy dogs. Microarray data revealed the presence of several tetracycline, erythromycin, aminoglycoside, and copper resistance genes; however, most of these originated from one animal with history of chronic skin infection two year prior to our sampling. Higher prevalence of antimicrobial resistance in pyoderma infected dogs may be related to stress; however, this requires further investigation. In conclusion, based on our data, healthy and pyoderma infected dogs do not represent an important reservoir of clinically significant antibiotic resistant microbiota.
Keywords: Dogs; Enterococci; Antibiotic resistant; bTEFAP; Microarray; Veterinary Medicine (0778)